Synthesis of arrays containing porphyrin, chlorin, and perylene-imide constituents for panchromatic light-harvesting and charge separation. Issue 42 (29th June 2018) - Hu, Gongfang; Kang, Hyun Suk; Mandal, Amit Kumar; Roy, Arpita; Kirmaier, Christine; Bocian, David F.; Holten, Dewey; Lindsey, Jonathan S.
Abstract : Twelve arrays containing porphyrin, chlorin, and/or perylene-imide units were synthesized to investigate panchromatic absorption integrated with charge separation. Abstract : Achieving solar light harvesting followed by efficient charge separation and transport is an essential objective of molecular-based artificial photosynthesis. Architectures that afford strong absorption across the near-UV to near-infrared region, namely panchromatic absorptivity, are critically important given the broad spectral distribution of sunlight. A tetrapyrrole–perylene pentad array was synthesized and investigated as a means to integrate panchromatic light harvesting and intramolecular charge separation. The pentad consists of three moieties: (1) a panchromatically absorbing triad, in which a porphyrin is strongly coupled to two perylene-monoimides via ethyne linkages; (2) a perylene-diimide electron acceptor; and (3) a chlorin hole-trapping unit. Integrating the three components with diphenylethyne linkers generates moderate electronic coupling for intramolecular energy and hole/electron transfer. The construction of the array relies on a stepwise strategy for incorporating modular pigment building blocks. The key building blocks include a trans -A2 BC porphyrin, a chlorin, a perylene-monoimide, and a perylene-diimide, each bearing appropriate (halo, ethynyl) synthetic handles for Pd-catalyzed Sonogashira coupling reactions. One target pentad, three tetrads, four triads, and four monomeric benchmark compounds were synthesized from six building blocks (three new, three reported) and 10 new synthetic intermediates. Four of the tetrapyrrole-containing arrays are zinc chelated, and four others are in the free base form. Absorption and fluorescence spectra and fluorescence quantum yields were also measured. Collectively, investigations of the arrays reveal insights into principles for the design of novel reaction centers integrated with a panchromatic antenna for artificial photosynthetic studies.